Determination of plastic limit of soil using modified cone penetration method - A. Rashid, Ahmad Safuan (2005)
Plastic limit is an important property of fine-grained soils. The standard threadrolling method for determining the plastic limit has long been criticized for requiring considerable judgments from the operator. Therefore, this study is conducted to introduce a new method on determining the plastic limit value using the cone penetration method similar to the liquid limit test but with slight modification on the size and the weight of cone. This is to overcome the inconsistence in the standard thread-rolling method to achieve the plastic limit. Three different types of cone with different sizes and weight have been fabricated and tested to determine the plastic limit values. These values were compared with the standard thread-rolling method. Cone (i) is based on the current study with the cone weight of 101.47g and cone angle of 20o. Cone (ii) is proposed by Wood and Wroth (1978) with the cone weight of 240g and cone angle of 30o. Cone (iii) proposed by Tao-Wei Feng (2004) is based on the weight of cone of 80g and angle of cone of 30o with small container; 20-mm diameter and 20-mm deep. Four soil samples from different part of Johor with Plasticity Index (PI) values ranging from 15 to 30 were tested. The soils are Kota Tinggi black clay, Kulai white clay, Kota Tinggi red clay and kaolin clay. Results indicated that, the regression analyses between plastic limit values obtained from thread rolling method and all the cone penetration methods were ranged from 0.9163 to 0.9943. This indicates that all the cones are feasible of performing the plastic limit test. However cone (i) gives the best correlation with the standard thread rolling method compared to other cone methods.